TikTok Shop Dalam Lensa Ekonomi Politik: Menilik dari Pendekatan Smithian dan Keynesian - Fazira, Arni (UIR Press, 2024)
TikTok Shop is one of the buying and selling platforms that is often used by the Indonesian people. However, TikTok Shop was closed in September 2023 because it did not have an official trading permit from e-commerce and did not meet the requirements as an e-commerce actor, before finally being reopened in December 2023. This study aims to analyze the TikTok Shop phenomenon from a political economy perspective using the Smithian and Keynesian approaches. The research method used is qualitative using literature studies. The results of this study indicate that before the closure, TikTok Shop operations reflected the Smithian free market principle with minimal government intervention. However, the closure and reopening of TikTok Shop with stricter regulations illustrate the Keynesian approach, where the government takes an active role in regulating the market to protect national economic interests. TikTok's partnership with Tokopedia after the regulation shows an effort to adjust to government policies. The findings in this study also state that government intervention aims to create a balance between the benefits of the free market and the protection of the local economy in the context of a rapidly growing digital economy.